Improvement of fatty acid profile and studio of rheological and technological characteristics in breads supplemented with flaxseed, soybean, and wheat bran flour - Osuna, Mariana Beatriz (2014)
Functional breads constitute an interesting alternative as vehicle of new essential fatty acids sources. The aim of this study was to improve the fatty acids (FA) profile of bakery products, producing breads with low saturated fatty acid (SFA) content and with high polyunsaturated fatty acid (PUFA) content, through partial substitution of wheat flour by other ingredients (soy flour, flax flour, and wheat bran) and to analyze the effect of this change on the technological, rheological, and sensorial characteristics of breads. Flaxseed flour (FF), soybeans flour (SF), or wheat bran (WB) was used to replace 50, 100, and 150 g kg−1 of wheat flour (WF) in breads. FF or SF produced a decrease in monounsaturated and SFA and an increase of PUFA in these breads. Furthermore, breads replaced with FF presented considerable increase in the content of n3 FA, while, SF or WB contributed to rise of linoleic and oleic FA, respectively. The substitution percentage increase of FF, SF, or WB to formulation produced changes in the colour, rheological, textural, and technological characteristics of breads. This replacement resulted in improved lipid profile, being breads with 50 g kg−1 SF, the better acceptance, baking features, and enhanced fatty acid profile.